Structure of the Dioxygenase AsqJ: Mechanistic Insights into a One‐Pot Multistep Quinolone Antibiotic Biosynthesis. Issue 1 (10th November 2015) - Bräuer, Alois; Beck, Philipp; Hintermann, Lukas; Groll, Michael
Abstract: Multienzymatic cascades are responsible for the biosynthesis of natural products and represent a source of inspiration for synthetic chemists. The Fe II /α‐ketoglutarate‐dependent dioxygenase AsqJ from Aspergillus nidulans is outstanding because it stereoselectively catalyzes both a ferryl‐induced desaturation reaction and epoxidation on a benzodiazepinedione. Interestingly, the enzymatically formed spiro epoxide spring‐loads the 6, 7‐bicyclic skeleton for non‐enzymatic rearrangement into the 6, 6‐bicyclic scaffold of the quinolone alkaloid 4′‐methoxyviridicatin. Herein, we report different crystal structures of the protein in the absence and presence of synthesized substrates, surrogates, and intermediates that mimic the various stages of the reaction cycle of this exceptional dioxygenase. Abstract : Multitalented : Crystallographic analysis gave detailed structural insight into the complex one‐pot multistep reaction catalyzed by the Fe II /α‐ketoglutarate‐dependent dioxygenase AsqJ. A ferryl‐induced desaturation reaction and epoxidation is followed by a non‐enzymatic elimination/rearrangement to give the quinolone alkaloid 4′‐methoxyviridicatin.